"The transformative power of Europe" beyond enlargement: the EU's performance in promoting democracy in its neighbourhood*. Issue 1 (2nd January 2017) - Börzel, Tanja A.; Lebanidze, Bidzina
ABSTRACT: This paper argues that the European Union's (EU) performance in promoting democracy in its neighbourhood is not only compromised by the lack of a membership perspective but the selective sanctioning of non-compliance with democracy standards caused by conflicting foreign policy objectives. We identify two conditions for the EU's consistent application of democratic conditionality: the absence of a stability-democratisation dilemma and the presence of pro-democratic reform coalitions. If neither of these conditions is present, the EU is more likely to act as a status-quo than a transformative power prioritising (authoritarian) stability over uncertain (democratic) change.